Special welding rod with high hardness and low cracking property

By adding specific raw materials and rare earth oxides to the welding rod coating to adjust the melting point and viscosity of the weld, the problems of low hardness and easy cracking of the welding rod are solved, and the weld with high hardness and low cracking are achieved, simplified the welding process and extended the The service life of the air hammer body meets the requirements of circular economy.

CN119188016APending Publication Date: 2024-12-27TANGSHAN LANYAN WELDING MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411594564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing welding rods have problems of low hardness and easy cracking when welding the gas hammer body, which leads to large energy consumption, complexity and increased economic losses during the repair process, and it is difficult to effectively solve the problem of repairing the cast iron hammer body explosion.

Method used

Special welding rods with high hardness and low cracking properties are used. The skin is composed of white soil, fluorite, titanium dioxide, iron titanium titanium, iron molybdenum, high carbon ferromanganese, ferrosilicon, metal nickel and rare earth oxides. By adjusting the CaF2 content in fluorite , add metal nickel and rare earth oxides, use potassium-sodium water glass as binder, combine with anatase titanium dioxide and rutile titanium dioxide to adjust the melting point and viscosity of the slag, reduce hydrogen content and crack generation, improve the hardness of the weld and crack resistance performance.

Benefits of technology

It has achieved the reduction of the risk of weld cracking, improved weld hardness and crack resistance, reduced energy consumption, simplified welding process, extended the service life of cast iron hammer body, solved the problem of cracking and repair of air hammer body, and conformed to the circulation Economic requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of welding materials, and provides a high-hardness low-cracking special welding rod which comprises a core wire and a coating wrapping the core wire, the coating comprises, by weight, 3%-6% of white clay, 20%-30% of fluorite, 6%-8% of titanium dioxide, 4%-7% of ferrotitanium, 2%-5% of ferromolybdenum, 1%-3% of high-carbon ferromanganese, 1%-3% of ferrosilicon, 4%-7% of rare earth oxide, 10%-14% of metallic nickel and the balance marble, and the core wire is an H08A steel welding wire; the content of CaF2 in the fluorite ranges from 90 wt% to 97 wt%. By means of the technical scheme, the problems that in the related technology, weld joints are low in hardness and prone to cracking are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding materials, and in particular to a special welding rod with high hardness and low cracking properties. Background Art

[0002] Welding rod is a material that plays a key role in the welding process. It usually consists of a metal welding core and a coating wrapped around the welding core. Welding rod mainly plays the role of connection, metallurgy and protection, and is widely used in construction, machinery manufacturing and other fields.

[0003] In modern industrial production, pneumatic hammers, as an important tool, play a key role in many fields due to their diverse types and wide applications. However, there are some key issues in the manufacturing materials and use of pneumatic hammers, which require our in-depth discussion. The hammer body of the pneumatic hammer is usually made of ductile cast iron instead of cast steel. This is mainly because cast iron has some unique advantages. First, from a cost perspective, cast iron can significantly reduce production costs, which is crucial for companies that use pneumatic hammers on a large scale and have high requirements for cost control; secondly, cast iron has special physical properties compared to cast steel. The tensile strength and hardness of cast iron are relatively small, but this feature makes it less likely to deform in practical applications. During the operation of the pneumatic hammer, it will be subjected to greater impact and vibration. The stability of cast iron can better adapt to the working environment, ensure the shape and structural integrity of the hammer body, and thus extend the service life of the pneumatic hammer.

[0004] There are two main reasons for the explosion of the pneumatic hammer body. On the one hand, it is overload fatigue use. The overload hammer body phenomenon is due to the large vibration force during long-term use, and the actual load far exceeds the original design load. In this case, the hammer body is under too much pressure and gradually explodes. The over-fatigue of the hammer body is determined by its working nature. When the pneumatic hammer is working, fatigue cracks will occur in the parts where the large vibration force is concentrated. With the increase of working time and the number of actions, the cracks continue to accumulate. When the number of cracks exceeds its limit stress, large cracks will appear. On the other hand, the weight seat is unstable. The weight seat is unstable due to improper operation of the workers. The weight is not in the right position, causing the pneumatic hammer to deviate, and then the cylinder body explodes. This is a problem caused by human factors, but it is more common in actual production.

[0005] Large-scale pneumatic hammers are expensive and widely used throughout the country and the world. Once the hammer explodes, if it is not replaced in time and there are no spare parts, it will seriously affect normal production and cause huge economic losses to the company. Therefore, direct on-site repair welding is a common solution, which not only meets the requirements of "green remanufacturing", but also reduces the replacement time, installation and new equipment costs for enterprises. However, there are many difficulties in the repair process of large-scale pneumatic hammers. With traditional surfacing electrodes, even if the hammer is preheated before welding (about 400°C) and heat treated after welding, the tendency of cracking within 5mm of the heat-affected zone during surfacing is still very large. At the same time, preheating before welding and heat treatment after welding will not only waste a lot of energy and make the welding process complicated, but also increase the labor intensity of manual labor, causing considerable economic losses to the company.

[0006] Therefore, a special welding rod with high hardness and low cracking is developed to perform surfacing welding on the cast iron hammer body, which not only reduces energy consumption and avoids environmental pollution during the manufacturing process, but also restores the original service life of the scrapped cast iron hammer body through preheating-free and heat-treatment-free surfacing welding. It also has important engineering significance for solving the problem of cast iron hammer body explosion and irreparable damage that is common in various industries such as metallurgical machinery, mining machinery, agricultural machinery, and petrochemical machinery in China. The market space is very broad, which is in line with the national policy of circular economy, energy conservation and emission reduction. Summary of the invention

[0007] The invention provides a special welding rod with high hardness and low cracking property, which solves the problem of low hardness and easy cracking of the welding seam in the related art.

[0008] The technical solution of the present invention is as follows: The present invention provides a special welding rod with high hardness and low cracking, comprising a welding core and a coating coated outside the welding core, wherein the coating is composed of the following raw materials in weight percentage: 3% to 6% of white clay, 20% to 30% of fluorite, 6% to 8% of titanium dioxide, 4% to 7% of ferrotitanium, 2% to 5% of ferromolybdenum, 1% to 3% of high carbon ferromanganese, 1% to 3% of ferrosilicon, 4% to 7% of rare earth oxide, 10% to 14% of metallic nickel, and the balance is marble, and the welding core is H08A steel welding wire; The content of CaF2 in the fluorite is in the range of 90wt% to 97wt%.

[0009] As a further technical solution, the rare earth oxide includes one or more of cerium oxide, lanthanum oxide, and yttrium oxide.

[0010] In the present invention, the addition of rare earth oxide as a raw material, preferably yttrium oxide, helps to improve the crystal structure after welding, reduce the deteriorated inclusions, and thus improve the crack resistance of the cladding metal.

[0011] As a further technical solution, the ferrosilicon is purified ferrosilicon, the purification temperature is 720-750° C., and the insulation time is 0.8-1.2 h.

[0012] As a further technical solution, the high carbon ferromanganese is purified high carbon ferromanganese, the purification temperature is 300-350°C, and the insulation time is 0.8-1.2h.

[0013] The present invention also proposes a method for preparing a special welding rod with high hardness and low cracking resistance, comprising the following steps: weighing the raw materials of the coating weight percentage, mixing them evenly, applying a binder on the welding core, drying and grinding, and obtaining the special welding rod with high hardness and low cracking resistance.

[0014] As a further technical solution, the drying temperature is 250-300°C.

[0015] As a further technical solution, the binder includes one or both of water glass and clay.

[0016] As a further technical solution, the water glass includes one or more of sodium water glass, potassium water glass, and potassium-sodium water glass.

[0017] As a further technical solution, when the water glass is potassium-sodium water glass, the modulus of the potassium-sodium water glass is 2.8-3.1; and the molar ratio of potassium element to sodium element in the potassium-sodium water glass is 2:1.

[0018] In the present invention, by limiting the modulus of water glass, it is helpful to adjust the viscosity and melting point of the slag, which can effectively prevent harmful gases such as oxygen and nitrogen from entering the molten pool, reduce the formation of pores and oxide and nitride inclusions in the weld, and thus improve the hardness and crack resistance of the weld.

[0019] In the present invention, the molar ratio of potassium element to sodium element in potassium-sodium water glass is adjusted, so that the slag has better fluidity and coverage during the welding process, promotes the refinement of weld metal grains, improves the hardness of the weld, adjusts the solidification speed and mode of the molten pool, makes the molten pool solidify more uniformly, reduces the concentration of shrinkage stress during the solidification process, reduces the risk of weld cracking, and enhances the anti-cracking performance of the weld.

[0020] As a further technical solution, the titanium dioxide is composed of anatase titanium dioxide and rutile titanium dioxide, and the mass ratio of the anatase titanium dioxide to the rutile titanium dioxide is 2:5-6.

[0021] In the present invention, anatase titanium dioxide and rutile titanium dioxide are added as raw materials at the same time, and the synergistic effect of the two is brought into play to promote the uniform distribution of internal stress of the material, reduce the generation of cracks, and improve the hardness of the weld.

[0022] As a further technical solution, the iron content of the ferrotitanium is 30wt%~80wt%, the molybdenum content of the ferromolybdenum is 60wt%~90wt%; the carbon content of the high carbon ferromanganese is 6wt%~7wt%; and the silicon content of the ferrosilicon is 70wt%~75wt%.

[0023] The working principle and beneficial effects of the present invention are: 1. In the present invention, marble, fluorite, clay and the like are used as raw materials to play the role of slag making and deoxidation. By limiting the content of CaF2 in fluorite, the melting point and viscosity of the slag are adjusted, which is beneficial to the crystallization of the weld metal, thereby improving the hardness of the weld. In the welding process, hydrogen is one of the important factors leading to weld cracking. CaF2, as the main dehydrogenation component, can reduce the hydrogen content in the weld, reduce the generation of hydrogen-induced cracks, and improve the crack resistance of the weld.

[0024] 2. In the present invention, adding metallic nickel as one of the raw materials can improve the stability of austenite in the cladding metal, improve the cladding structure, improve the distribution state of residual stress, and improve the crack resistance of the weld.

[0025] 3. In the present invention, an appropriate amount of ferromolybdenum is added to ensure that the cladding metal has a certain degree of hardness, and an appropriate amount of ferrotitanium, ferromanganese and ferrosilicon are added for deoxidation and alloying to improve the hardness of the weld. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following examples and comparative examples: Marble: particle size is 400 mesh; White clay: particle size is 400 mesh; Fluorite: CaF2 content is 90wt%, particle size is 325 mesh; Ferro-titanium: iron content is 40wt%; Ferromolybdenum: Molybdenum content is 60wt%; High carbon ferromanganese: carbon content is 7wt%; Ferrosilicon: Silicon content 75wt%; Cerium oxide: average particle size is 1.5 μm; Lanthanum oxide: average particle size is 1 μm; Yttrium oxide: average particle size is 1 μm; Metal nickel: purity is 99.99%; Clay: Kaolin clay, particle size 325 mesh, silica content 65wt%; Welding core: H08A steel welding wire, diameter 2mm; Coating: thickness 1mm; Anatase titanium dioxide: average particle size 20nm; Rutile titanium dioxide: average particle size 20nm.

[0028] Example 1 A special welding rod with high hardness and low cracking property, comprising a welding core and a coating covering the welding core, wherein the coating comprises the following raw materials in percentage by weight: 3% white clay, 20% fluorite, 6% titanium dioxide, 4% ferrotitanium, 2% ferromolybdenum, 1% high carbon ferromanganese, 1% ferrosilicon, 4% cerium oxide, 10% nickel metal, and the balance is marble, wherein the content of CaF2 in the fluorite is 90wt%; wherein the titanium dioxide is anatase titanium dioxide; The welding core is H08A steel welding wire; Ferrosilicon is purified at 720°C with a holding time of 1.2 h, and high carbon ferromanganese is purified at 300°C with a holding time of 1.2 h. The raw materials for the coating are prepared according to the above weight percentages, mixed evenly by a roller, and then water glass (the amount added is 5% of the total weight of the coating) is added and stirred evenly. The welding rod is extruded by a welding rod coating machine, and the welding rod is dried at 250°C and then ground to obtain a special welding rod with high hardness and low cracking resistance, wherein the water glass is sodium water glass with a modulus of 2.6~2.8m.

[0029] Example 2 A special welding rod with high hardness and low cracking property, comprising a welding core and a coating covering the welding core, wherein the coating comprises the following raw materials in percentage by weight: 3.5% white clay, 22.7% fluorite, 7% titanium dioxide, 5.8% ferrotitanium, 2.6% ferromolybdenum, 2.5% high carbon ferromanganese, 1.6% ferrosilicon, 5.3% cerium oxide, 13.1% metallic nickel, and the balance is marble, wherein the content of CaF2 in the fluorite is 90wt%; wherein the titanium dioxide is anatase titanium dioxide; The welding core is H08A steel welding wire; Ferrosilicon is purified at 730°C for 1 hour, and high carbon ferromanganese is purified at 320°C for 1 hour. The raw materials of the coating are prepared according to the above weight percentage, mixed evenly by a roller, and then water glass (the amount added is 5% of the total weight of the coating) is added and stirred evenly. The welding rod is extruded by a welding rod coating machine, and the welding rod is dried at 280°C and then ground to obtain a special welding rod with high hardness and low cracking, wherein the water glass is sodium water glass with a modulus of 2.6~2.8m.

[0030] Example 3 A special welding rod with high hardness and low cracking property, comprising a welding core and a coating covering the welding core, wherein the coating comprises the following raw materials in percentage by weight: 6% white clay, 30% fluorite, 8% titanium dioxide, 7% ferrotitanium, 5% ferromolybdenum, 3% high carbon ferromanganese, 3% ferrosilicon, 7% cerium oxide, 14% metallic nickel, and the balance is marble, wherein the content of CaF2 in the fluorite is 90wt%; wherein the titanium dioxide is anatase titanium dioxide; The welding core is H08A steel welding wire; Ferrosilicon is purified at 750°C with a holding time of 0.8h, and high carbon ferromanganese is purified at 350°C with a holding time of 0.8h. The raw materials for the coating are prepared according to the above weight percentages, mixed evenly by a roller, and then water glass (the amount added is 5% of the total weight of the coating) is added and stirred evenly. The welding rod is extruded by a welding rod coating machine, and the welding rod is dried at 300°C and then ground to obtain a special welding rod with high hardness and low cracking, wherein the water glass is sodium water glass with a modulus of 2.6~2.8m.

[0031] Example 4 Compared with Example 2, the difference of Example 4 is that the content of CaF2 in fluorite is 95wt%.

[0032] Example 5 Compared with Example 2, the difference in Example 5 is that the content of CaF2 in fluorite is 97wt%.

[0033] Example 6 Compared with Example 4, Example 6 is different in that cerium oxide is replaced by an equal amount of lanthanum oxide.

[0034] Example 7 Compared with Example 4, Example 7 is different in that cerium oxide is replaced by an equal amount of yttrium oxide.

[0035] Example 8 Compared with Example 7, Example 8 is different in that water glass is replaced by an equal amount of clay.

[0036] Example 9. Compared with Example 7, the difference of Example 9 is that the sodium water glass is replaced by an equal amount of potassium water glass, and the modulus is 2.6-2.8m.

[0037] Example 10 Compared with Example 7, the difference of Example 10 is that sodium water glass is replaced by an equal amount of potassium sodium water glass, wherein the modulus of potassium sodium water glass is 2.5~2.7m, and the molar ratio of potassium element to sodium element is 1:1.

[0038] Embodiment 11 Compared with Example 10, the difference of Example 11 is that the modulus of sodium-potassium water glass is 2.8~3.0m.

[0039] Example 12 Compared with Example 10, the difference in Example 12 is that the modulus of sodium-potassium water glass is 3.15-3.25 m.

[0040] Example 13 Compared with Example 12, the difference of Example 13 is that the molar ratio of potassium element to sodium element in potassium-sodium water glass is 2:1.

[0041] Embodiment 14 Compared with Example 12, the difference of Example 14 is that the molar ratio of potassium element to sodium element in potassium-sodium water glass is 3:1.

[0042] Embodiment 15 Compared with Example 13, the difference in Example 15 is that the titanium dioxide is rutile titanium dioxide.

[0043] Example 16 Compared with Example 13, the difference of Example 16 is that the titanium dioxide is composed of anatase titanium dioxide and rutile titanium dioxide in a mass ratio of 2:5.

[0044] Embodiment 17 Compared with Example 13, the difference of Example 17 is that the titanium dioxide is composed of anatase titanium dioxide and rutile titanium dioxide in a mass ratio of 2:6.

[0045] Comparative Example 1 Compared with Example 2, the difference in Comparative Example 1 is that the content of CaF2 in fluorite is 85wt%.

[0046] Comparative Example 2 Compared with Example 2, the difference of Comparative Example 2 is that the content of CaF2 in fluorite is 99wt%.

[0047] The special welding rods prepared in Examples 1 to 17 and Comparative Examples 1 to 2 were used to repair the cracks of the hammer body of the gas hammer by surfacing welding. The welding rods were dried at 300° C. for 1 hour before welding to remove the crystal water in the coating. A DC welding machine was used for reverse connection. The welding current was 150-200A and the welding voltage was 70-80V. The hammer body was not preheated before welding and no heat treatment was performed after welding. The repaired hammer body was tested according to the following method: 1. Brinell hardness: Test the Brinell hardness of the sample according to the single-point determination test method specified in GB / T 2654-2008 "Test method for hardness of welded joints".

[0048] 2. Diffusible hydrogen content: Test the diffusible hydrogen content of the sample according to the thermal conductivity method specified in GB / T 3965-2012 "Determination of diffusible hydrogen in deposited metal".

[0049] 3. Cracking test: Observe the cracks on the surface of the hammer.

[0050] The test results are shown in the following table: Table 1 Application performance test results of special welding rods prepared in Examples 1 to 17 and Comparative Examples 1 to 2

[0051] Compared with Examples 2, 4, and 5, the content of CaF2 in fluorite in Comparative Example 1 is 85wt%, and the content of CaF2 in fluorite is 99wt%. As a result, the Brinell hardness of Examples 2, 4, and 5 is higher than that of Comparative Examples 1 and 2, the diffusible hydrogen content is lower than that of Comparative Examples 1 and 2, and the crack condition on the surface of the hammer is also better than that of Comparative Examples 1 and 2, indicating that when the content of CaF2 in fluorite ranges from 90wt% to 97wt%, and the preferred content range is 95wt%, the obtained special welding rod has a higher weld hardness and better crack resistance.

[0052] Compared with Example 4, Examples 6 and 7 add different rare earth oxides. As a result, the Brinell hardness of Example 7 is higher than that of Examples 4 and 6, and the diffusible hydrogen content is lower than that of Examples 4 and 6, indicating that when the added rare earth oxide is yttrium oxide, the hardness and crack resistance of the weld can be improved.

[0053] Compared with Example 8, Example 7 adds water glass as a binder. As a result, the Brinell hardness of Example 7 is higher than that of Example 8, and the diffusible hydrogen content is lower than that of Example 8, indicating that when water glass is used as the binder, the hardness and crack resistance of the weld can be improved.

[0054] Compared with Example 7, Examples 9 and 10 add different types of water glass. As a result, the Brinell hardness of Example 10 is higher than that of Examples 7 and 9, and the diffusible hydrogen content is lower than that of Examples 7 and 9, indicating that when the added water glass is potassium-sodium water glass, the weld hardness of the obtained special welding rod is higher and the crack resistance is better.

[0055] Compared with Example 10, Examples 11 and 12 add potassium-sodium water glasses with different moduli. As a result, the Brinell hardness of Example 11 is higher than that of Examples 10 and 12, and the diffusible hydrogen content is lower than that of Examples 10 and 12, indicating that when the modulus of the added potassium-sodium water glass is 2.8-3.1, the weld hardness of the obtained special welding rod is higher and the crack resistance is better.

[0056] Compared with Example 11, Examples 13 and 14 added potassium-sodium waterglass with different molar ratios of potassium element to sodium element. As a result, the Brinell hardness of Example 13 was higher than that of Examples 11 and 14, and the diffusible hydrogen content was lower than that of Examples 11 and 14, indicating that when the molar ratio of potassium element to sodium element in the potassium-sodium waterglass was 2:1, the obtained special welding rod had higher weld hardness and better crack resistance.

[0057] Compared with Example 15, Examples 16 and 17 simultaneously added anatase titanium dioxide and rutile titanium dioxide. As a result, the Brinell hardness of Examples 16 and 17 was higher than that of Example 15, and the diffusible hydrogen content was lower than that of Example 15, indicating that anatase titanium dioxide and rutile titanium dioxide play a synergistic role in improving the hardness and crack resistance of the weld.

[0058] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A special welding rod with high hardness and low cracking resistance, characterized in that: The invention comprises a welding core and a coating coated on the welding core, wherein the coating comprises the following raw materials in weight percentage: 3% to 6% kaolin, 20% to 30% fluorite, 6% to 8% titanium dioxide, 4% to 7% ferrotitanium, 2% to 5% ferromolybdenum, 1% to 3% high carbon ferromanganese, 1% to 3% ferrosilicon, 4% to 7% rare earth oxide, 10% to 14% metallic nickel, and the balance is marble; the welding core is H08A steel welding wire; the content of CaF2 in the fluorite ranges from 90wt% to 97wt%.

2. A high-hardness, low-cracking special welding rod according to claim 1, characterized in that: The rare earth oxide includes one or more of cerium oxide, lanthanum oxide and yttrium oxide.

3. A high-hardness and low-cracking special welding rod according to claim 1, characterized in that: The ferrosilicon is purified ferrosilicon, the purification temperature is 720-750° C., and the insulation time is 0.8-1.2 h.

4. A high-hardness and low-cracking special welding rod according to claim 1, characterized in that: The high carbon ferromanganese is purified high carbon ferromanganese, the purification temperature is 300-350° C., and the insulation time is 0.8-1.2 h.

5. The method for preparing a special welding rod with high hardness and low cracking resistance according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials of the coating are weighed according to the weight percentage, mixed evenly, pressed onto the welding core with a binder, and dried and polished to obtain a special welding rod with high hardness and low cracking.

6. The method for preparing a special welding rod with high hardness and low cracking resistance according to claim 5, characterized in that: The drying temperature is 250-300°C.

7. The method for preparing a special welding rod with high hardness and low cracking resistance according to claim 5, characterized in that: The binder includes one or both of water glass and clay.

8. The method for preparing a special welding rod with high hardness and low cracking resistance according to claim 7, characterized in that: The water glass includes one or more of sodium water glass, potassium water glass, and potassium-sodium water glass.

9. The method for preparing a special welding rod with high hardness and low cracking resistance according to claim 8, characterized in that: When the water glass is potassium-sodium water glass, the modulus of the potassium-sodium water glass is 2.8-3.1, and the molar ratio of potassium element to sodium element in the potassium-sodium water glass is 2:

1.

10. The method for preparing a special welding rod with high hardness and low cracking resistance according to claim 9, characterized in that: The titanium dioxide is composed of anatase titanium dioxide and rutile titanium dioxide, and the mass ratio of the anatase titanium dioxide to the rutile titanium dioxide is 2:5-6.

Citation Information

Patent Citations

  • Special welding electrode for surfacing and repairing broken teeth of cast iron gear

    CN101920404A

  • Special welding electrode for surfacing and repairing broken teeth of cast steel gear

    CN101920414A

  • Special welding rod for stack welding repair and reproduction of hot-forging die

    CN102240872A

  • Special welding electrode for surfacing and repairing broken teeth of light-load and low-speed gear

    CN102489891A

  • Special welding electrode for surfacing and repairing broken teeth of medium-load and medium-speed gear

    CN102489900A

Cited By

  • Welding rod for repairing surfacing welding of grey cast iron sintering pallet

    CN120228456A